Identificación de las políticas contables del servicio nacional de aguas subterráneas riego y avenamiento de acuerdo con el Plan General de Contabilidad Nacional y Elaboración de la Guía de Aplicación de Activos. - Chinchilla-Cruz, Yeison (Instituto Tecnológico de Costa Rica, 2014)
The purpose of this paper is to identify and extract the accounting policies of Assets, Liabilities, Capital, Expense, Income and Financial Statements that apply to transactions of the National Service of Groundwater, Irrigation and Drainage (Senara), autonomous and public institution for developing the Implementation Guide which facilitates the understanding of those policies. To achieve this purpose, an analysis has to be done of the following 2 aspects: the International Accounting Standards for the Public Sector, known as IPSAS to learn the current regulations and the General Plan of Annualized Accounting that shows general accountant policies, the Chart of Accounts and the Application Guide of accounting policies.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2014.
Keywords: Extracción; Función pública; Patrimonio; Ingresos; Gastos públicos; Estado; Mercado financiero